Decoupling QoS control from core routers a novel bandwidth broker architecture for scalable support of guaranteed services. - Zhang, Zhi-Li (Computer communication review.)
For scalable support of guaranteed services that decouples the QoS control plane from the packet forwarding plane. More specifically, under this architecture, core routers do not maintain any QoS reservation states, whether per-flow or aggregate. Instead, QoS reservation states are stored at and managed by bandwidth broker(s). There are several advantages of such a bandwidth broker architecture. Among others, it relieves core routers of QoS control functions such as admission control and QoS state management, and thus enables a network service provider to introduce new (guaranteed) services without necessarily requiring software/hardware upgrades at core routers. Furthermore, it allows us to design efficient admission control algorithms without incurring any overhead at core routers. The proposed bandwidth broker architecture is designed based on a core stateless virtual time reference system developed in [20].